PENGARUH LOKASI DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK AYAM D"™FRESTO DI GANG SAYUR PONTIANAK - Febrianty, Hasya; Witarsa, Witarsa; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to find out: 1) How does the influence of sales location on the purchasing decision of D'fresto chicken products in Alley Sayur Pontianak, 2) How does sales promotion influence the buying decision of D'fresto chicken products in Alley Sayur Pontianak, 3) how do they influence location and Sales Promotion on the Purchase Decision of D'fresto Chicken Products at Alley Sayur Pontianak Simultaneously. Multiple Linear Regression Analysis is the research approach used, together with a quantitative research form. 84 customers make up the study's sample. The study's findings indicate that: 1) 3,143 purchase choices are significantly influenced by location, with a significant value of 0.002 0.05. At a significance level of 0.000 0.05, sales promotion has a considerable impact on purchase decisions with a 4.869 score. 3) With a F value of 42.355 at a significance level of 0.000, it was discovered that location and sales promotion had a substantial simultaneous influence on choices to buy D'fresto chicken items in Alley Sayur Pontianak. has a 51.1% magnitude of effect, whilst other variables not included in this research have an impact on the remaining 48.9%.